Pengaruh Kompetensi Kepribadian Guru, Motivasi Dan Lingkungan Kerja Terhadap Kinerja Guru Di Gugus 2 Gerung, Kecamatan Gerung, Kabupaten Lombok Barat - Nurul Hakiki Sabila; Bahtiar; Badrun (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The study aims to determine the influence of teacher personality competence on teacher performance, the influence of motivation on teacher performance, the influence of the work environment on teacher performance, and the combined influence of teacher personality competence, motivation, and work environment on teacher performance in Cluster 2. The study adopts a quantitative approach using a survey research method and an experimental research design. Data collection is conducted using a questionnaire technique. The population of this study consists of all teachers in Cluster 2, totaling 45 individuals. The sample is selected using the census of saturation sampling method, resulting in a sample size equal to the population, which is 45 individuals. Data collection is performed through questionnares, and data analysis includes descriptive analysis, multiple linear regression analysis, t-test, and F-test. The findings of this study indicate that teacher personality competence has significant influence on teacher performance in Cluster 2, as the significance value (t) is 0,000, which is smaller than α= 0,005, with a regression coefficient of 0,332. The work environment has a significant influence on teacher performance in Cluster 2, as the significance value (t) is 0,000, which is smaller than α= 0,005, with a regression coefficient of 0,223. Furthermore, the combined influence of teacher personality competence, motivation, and work environment significantly affect teacher performance in Cluster 2.